A new unidirectional carbon fiber prepreg using physically modified epoxy matrix with cellulose nano fibers and spread tows. (November 2016) - Umeki, Ryo; Tanaka, Aya; Okubo, Kazuya; Fujii, Toru; Kawabe, Kazumasa; Kondo, Keiichi; Yamazaki, Takeshi; Hamada, Kenichi; Harada, Tetsuya
Abstract: A new unidirectional carbon fiber prepreg was successfully developed, whose epoxy matrix was physically modified with cellulose nano fibers (CNF). Two different types of prepreg were fabricated using regular carbon fiber (CF) and spread CF tows to identify the effect of prepreg thickness on the mechanical performance including fatigue of quasi isotropic laminates using these prepregs while the thickness of each layer was kept the same (120 μm). The effect of CNF modification of epoxy matrix on the fatigue life is quite significant if thin prepregs were used. It increases greater than 10 times than the fatigue lives of laminates fabricated by regular CF tows/unmodified EP or regular CF tows/modified EP. Uniformly dispersed CNF in the epoxy matrix increases the interfacial strength between CF and matrix.